2002
DOI: 10.1111/1468-2397.00204
|View full text |Cite
|
Sign up to set email alerts
|

The political participation of social workers: a comparative study

Abstract: This article reports on a comparative study that examined the political participation of social workers in KwaZulu‐Natal province in South Africa, the state of New South Wales (excluding the Hunter region) in Australia, and New Zealand. Each of these contexts had roughly the same number of social workers, that is, approximately 1,200. It was found that social workers in New Zealand tended to be more politically active than their counterparts in New South Wales and KwaZulu‐Natal, and the reasons for this are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 4 publications
1
42
0
3
Order By: Relevance
“…The AASW's CPE programme needs to provide opportunities for social workers to develop an acute awareness of the political context in which their actions take place and the political consequences of their actions (Gray 2002). Without those opportunities, the AASW may, by omission, reinforce prevailing ideologies.…”
Section: Resultsmentioning
confidence: 99%
“…The AASW's CPE programme needs to provide opportunities for social workers to develop an acute awareness of the political context in which their actions take place and the political consequences of their actions (Gray 2002). Without those opportunities, the AASW may, by omission, reinforce prevailing ideologies.…”
Section: Resultsmentioning
confidence: 99%
“…Giving the lack of comparable studies employing similar methodological tools on social worker participation in parliamentary committees in other welfare states, it is unclear whether there is a similar degree of involvement in parliamentary committees in other national contexts. While in the existing literature on the participation of social workers in the policy process in different countries (Ezell 1994, Gray et al. 2002, Dudziak & Coates 2004, Figueira‐McDonough 2007) does indeed report on testifying before public hearings and state commissions, these studies draw upon either the retrospective self‐reported data of social workers or on specific case studies of the involvement of social workers in the legislative stages of policy process.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen demographic questions were used to gather information about participants’ personal and professional backgrounds, including level of education, number of years licensed, practice location and context, and professional organization membership. Twenty‐nine items covering Dietz Domanski's () domains of policy engagement were adapted from an investigation of the political participation of social workers (Gray et al., ). The survey consisted of yes/no questions about policy advocacy (e.g., “Have you ever advocated for governmental policy change for a client?”), organizational advocacy (e.g., “Have you ever made efforts in a professional capacity to influence opinion among coworkers about an agency or workplace problem?”), and political participation (e.g., “In the past 5 years, have you actively volunteered or worked for a political party?”).…”
Section: Methodsmentioning
confidence: 99%
“…Following the method used by Gray et al. (), we analyzed the data with descriptive statistics, reporting frequencies, and mean scores. To explore the data from the open‐ended question, we used Braun and Clarke's () six‐phase thematic analysis.…”
Section: Methodsmentioning
confidence: 99%